Loading in 5 sec....

I. Review Distribute (aka F.O.I.L.)PowerPoint Presentation

I. Review Distribute (aka F.O.I.L.)

- 98 Views
- Uploaded on

Download Presentation
## PowerPoint Slideshow about ' I. Review Distribute (aka F.O.I.L.)' - faunus

**An Image/Link below is provided (as is) to download presentation**

Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.

- - - - - - - - - - - - - - - - - - - - - - - - - - E N D - - - - - - - - - - - - - - - - - - - - - - - - - -

Presentation Transcript

### I. Review Distribute (aka F.O.I.L.)II. Review Trial and ErrorIII. Review GroupingIII. Factoring Quadratics

Factoring Steps for Trial and Error

x2 + 5x + 6

Factoring Steps for Trial and Error

x2 + 5x + 6

1x2 + 5x + 6

(1x – 1) (1x + 6 ) F.O.I.L. to check answer

Factoring Steps for Trial and Error

x2 + 5x + 6

1x2 + 5x + 6

(1x – 1) (1x + 6 ) F.O.I.L. to check answer

(1x – 1) (1x + 6 ) = x2 + 5x – 6 Error, Try Again

Factoring Steps for Trial and Error

x2 + 5x + 6

Factoring Steps for Trial and Error

x2 + 5x + 6

1x2 + 5x + 6

(1x + 2) (1x + 3) F.O.I.L. to check answer

Factoring Steps for Trial and Error

x2 + 5x + 6

1x2 + 5x + 6

(1x + 2) (1x + 3) F.O.I.L. to check answer

(x + 2) (x + 3) = x2 + 5x + 6 Correct!

Factoring Steps for Trial and Error

3x2 – 4x – 4

Factoring Steps for Trial and Error

3x2 – 4x – 4

(3x + 1) (1x – 4 ) F.O.I.L. to check answer

(3x + 1) (1x – 4) = 3x2 – 11x – 4 Error, Try Again

Factoring Steps for Trial and Error

3x2 – 4x – 4

Factoring Steps for Trial and Error

3x2 – 4x – 4

(3x – 1) (1x + 4) F.O.I.L. to check answer

(3x – 1) (1x + 4) = 3x2 + 11x – 4 Error, Try Again

Factoring Steps for Trial and Error

3x2 – 4x – 4

Factoring Steps for Trial and Error

3x2 – 4x – 4

(3x + 2) (1x – 2 ) F.O.I.L. to check answer

(3x + 2) (1x – 2) = 3x2 – 4x – 4 Correct!

Factoring Steps for Trial and Error

– 6x2 – x + 2

Factoring Steps for Trial and Error

– 6x2 – x + 2

Wow! How are we going to factor this??

Well, let’s try another method and see if that

will help with this problem.

We can try Factoring by Grouping.

x2 + 5x + 6

x2 + 5x + 6

x2 + 2x + 3x + 6

x2 + 2x + 3x + 6

x(x + 2) +3(x + 2)

(x + 2) (x + 3)

3x2 – 4x – 4

3x2 – 4x – 4

3x2 – 6x + 2x – 4

3x2 – 6x + 2x – 4

3x(x – 2) + 2(x – 2)

(x – 2) (3x + 2)

3x2 – 4x – 4

3x2 – 6x + 2x – 4

3x2 – 6x + 2x – 4

3x(x – 2) 2(x – 2)

(x – 2) (3x + 2)

Or it can be factored this way . . .

3x2 – 4x – 4

3x2 – 4x – 4

3x2 + 2x – 6x – 4

3x2 + 2x – 6x – 4

x(3x + 2) – 2(3x + 2)

(3x + 2) (x – 2)

– 6x2 – x + 2

– 6x2 – x + 2

Oh, we are back to this problem again!

Do you think Trial & Error or Grouping

will work easily on this problem?

– 6x2 – x + 2

If you don’t think so, most people would agree with you.

What if I told you there was a different way that would work for the simple problems as well

as for problems like the one above?

1A. Factor out GCF, if necessary.

1B. Make x2 term positive, if necessary.

• Carry the GCF and / or – sign and put in front of ( ) ( ) in answer.

Do “Front times the Back” and get an answer.

“Front times the Back” means to multiply coefficient

of the x2 term (NUMBER ONLY NOT SIGN)

and the constant (NUMBER ONLY NOT SIGN).

3. Find the factors of the “Front times the Back’s”

answer that will add or subtract

to equal the middle term.

When these factors are multiplied,

the sign of that answer

must equal the

sign of the constant.

This step is very important because it

will eliminate the extraneous (extra) solutions.

5A. Separate the x2 into x • x.

5B. Write one x in the front of each ( )( ).

5C. Then write the factors in the back of each ( )( ).

example of answer:

(x + 3) (x + 5)

Divide only the numbers in the ( )( )

by the positive coefficient of x2.

Divide out common terms.

(aka: Simplify fractions.)

If there is a whole # left, that ( ) is finished.

If there is a fraction left, the denominator becomes the coefficient of x and the numerator is now the constant in the ( ).

Example: (x + 2) (x + ¾)

(x+2) ( 4x + 3) = answer

This is now in factored form.

Set each ( ) equal to 0 and solve for x.

Example: (x + 3) ( x + 5) = 0

x + 3 = 0 x + 5 = 0

x = 0 – 3 x = 0 – 5

x = – 3 x = – 5

If x equals – 3 or – 5, then at least one factor will be equal to 0 which will cause the left side to be 0. So 0 = 0 is true and the answer is x = {-3, -5}.

x2+ 5x + 6

1x2+ 5x + 6

1x2+ 5x + 6

Step 1: No GCF

Step 2:Step 3:

1 * 6 = 6 + 6 +3

1 * 6 – 1+2

2 * 3 + 5 +5

1x2+ 5x + 6

Step 1: No GCF

Step 2:Step 3:

1 * 6 = 6 + 6 +3

1 * 6 – 1+2

2 * 3 + 5 +5

Even though there are two ways to get +5, only one set of factors will work.

1x2+ 5x + 6

Step 1: No GCF

Step 2:Step 3:

1 * 6 = 6 + 6 +3

1 * 6 – 1+2

2 * 3 + 5 +5

Even though there are two ways to get +5, only one set of factors will work.

Step 4:

(+6)(–1) = – #

(+3)(+2) = + #, and the last term is a + #, so only the +3 and the +2 will work.

1x2+ 5x + 6

Step 1: No GCF

Step 5: (x + 2) (x + 3)

Step 2:Step 3:

1 * 6 = 6 + 6 +3

1 * 6 – 1+2

2 * 3 + 5 +5

Even though there are two ways to get +5, only one set of factors will work.

Step 4:

(+6)(–1) = – #

(+3)(+2) = + #, and the last term is a + #, so only the +3 and the +2 will work.

1x2+ 5x + 6

Step 1: No GCF

Step 5: (x + 2) (x + 3)

Step 6: (x + 2) (x + 3)

1 1

Step 2:Step 3:

1 * 6 = 6 + 6 +3

1 * 6 – 1+2

2 * 3 + 5 +5

Even though there are two ways to get +5, only one set of factors will work.

Step 4:

(+6)(–1) = – #

(+3)(+2) = + #, and the last term is a + #, so only the +3 and the +2 will work.

1x2+ 5x + 6

Step 1: No GCF

Step 5: (x + 2) (x + 3)

Step 6: (x + 2) (x + 3)

1 1

Step 7-9: (x + 2) (x + 3)

Step 2:Step 3:

1 * 6 = 6 + 6 +3

1 * 6 – 1+2

2 * 3 + 5 +5

Even though there are two ways to get +5, only one set of factors will work.

Step 4:

(+6)(–1) = – #

(+3)(+2) = + #, and the last term is a + #, so only the +3 and the +2 will work.

(x + 2) (x + 3) = 0

x + 2 = 0 x + 3 = 0

x = 0 – 2 x = 0 – 3

x = – 2 x = – 3

x = {– 2, – 3}

x2 – 5x – 6

1x2 – 5x – 6

1x2 – 5x – 6

Step 1: No GCF

Step 2:Step 3:

1 * 6 = 6– 6 – 3

1 * 6 + 1– 2

2 * 3 – 5 – 5

Even though there are two ways to get – 5, only one set of factors will work.

1x2 – 5x – 6

Step 1: No GCF

Step 2:Step 3:

1 * 6 = 6– 6 – 3

1 * 6 + 1– 2

2 * 3 – 5 – 5

Even though there are two ways to get – 5, only one set of factors will work.

Step 4:

(– 6)(+ 1) = – #

(– 3)(– 2) = + #, and the last term is a – #, so only the – 6 and the + 1 will work.

1x2 – 5x – 6

Step 1: No GCF

Step 5: (x – 6) (x + 1)

Step 2:Step 3:

1 * 6 = 6– 6 – 3

1 * 6 + 1– 2

2 * 3 – 5 – 5

Even though there are two ways to get – 5, only one set of factors will work.

Step 4:

(– 6)(+ 1) = – #

(– 3)(– 2) = + #, and the last term is a – #, so only the – 6 and the + 1 will work.

1x2 – 5x – 6

Step 1: No GCF

Step 5: (x – 6) (x + 1)

Step 6: (x – 6) (x + 1)

1 1

Step 2:Step 3:

1 * 6 = 6– 6 – 3

1 * 6 + 1– 2

2 * 3 – 5 – 5

Even though there are two ways to get – 5, only one set of factors will work.

Step 4:

(– 6)(+ 1) = – #

(– 3)(– 2) = + #, and the last term is a – #, so only the – 6 and the + 1 will work.

1x2 – 5x – 6

Step 1: No GCF

Step 5: (x – 6) (x + 1)

Step 6: (x – 6) (x + 1)

1 1

Step 7-9:(x – 6) (x + 1)

Step 2:Step 3:

1 * 6 = 6– 6 – 3

1 * 6 + 1– 2

2 * 3 – 5 – 5

Even though there are two ways to get – 5, only one set of factors will work.

Step 4:

(– 6)(+ 1) = – #

(– 3)(– 2) = + #, and the last term is a – #, so only the – 6 and the + 1 will work.

(x – 6) (x + 1) = 0

x – 6 = 0 x + 1 = 0

x = 0 + 6 x = 0 – 1

x = + 6 x = – 1

x = {+ 6, – 1}

2x2 + 7x – 4

2x2 + 7x – 4

Step 1: No GCF

Step 2:Step 3:

2 * 4 = 8 + 8

1 * 8 – 1

2 * 4 + 7

2x2 + 7x – 4

Step 1: No GCF

Step 2:Step 3:

2 * 4 = 8 + 8

1 * 8 – 1

2 * 4 + 7

Step 4:

Only the +8 added to the – 1 will equal +7.

And since (+ 8)(– 1) = – # , this verifies these are the two factors needed.

2x2 + 7x – 4

Step 1: No GCF

Step 5: (x + 8) (x – 1)

Step 2:Step 3:

2 * 4 = 8 + 8

1 * 8 – 1

2 * 4 + 7

Step 4:

Only the +8 added to the – 1 will equal +7.

And since (+ 8)(– 1) = – # , this verifies these are the two factors needed.

2x2 + 7x – 4

Step 1: No GCF

Step 5: (x + 8) (x – 1)

Step 6: (x + 8) (x – 1)

2 2

Step 2:Step 3:

2 * 4 = 8 + 8

1 * 8 – 1

2 * 4 + 7

Step 4:

Only the +8 added to the – 1 will equal +7.

And since (+ 8)(– 1) = – # , this verifies these are the two factors needed.

2x2 + 7x – 4

Step 1: No GCF

Step 5: (x + 8) (x – 1)

Step 6: (x + 8) (x – 1)

2 2

Step 7-9: (x + 4) (2x – 1)

Step 2:Step 3:

2 * 4 = 8 + 8

1 * 8 – 1

2 * 4 + 7

Step 4:

Only the +8 added to the – 1 will equal +7.

And since (+ 8)(– 1) = – # , this verifies these are the two factors needed.

(x + 4) (2x – 1)

x + 4 = 0 2x – 1= 0

x = 0 – 4 2x = 0 + 1

x = – 4 2x = 1

x = ½

x = { – 4, ½ }

practice problems. . .

x2 + 4x + 3

x2 + 4x + 3

Step 1: No GCF

Step 2: “Front times the Back”

Step 3A: What factors of 3 add to = +4? AND

Step 3B: Do signs multiply to equal a + #?

x2 + 4x + 3

x2+3x +1x + 3

- x2 + 4x + 3
- x2+3x +1x + 3
- Now separate the x2 into x • x
- Put each x into ( ) ( )
- Put the two red #s into ( ) ( )

1x2 + 4x + 3

x2+3x +1x + 3

( x +3) ( x +1)

1 1

Since dividing by 1 does not change the numbers, we have discovered that if the coefficient of x2 is 1, then we can eliminate the dividing by the x2 coefficient step.

3x2 - 4x – 4

3x2 - 4x – 4

(x + 2) (x – 6)

3x2 - 4x – 4

(x + 2) (x – 6)

(x + 2) (x – 6)

3 3

(3x + 2) (x – 2)

You are now ready for

The Problem ! ! ! ! !

– 6x2 – x + 2

– 6x2 – x + 2

Step 1A: No GCF

Step 1B: – 1(6x2 + x – 2)

Step 2:

6 * 2 = 12

1 * 12

2 * 6

3 * 4

– 6x2 – x + 2

Step 1A: No GCF

Step 1B: – 1(6x2 + x – 2)

Step 2:Step 3:

6 * 2 = 12 + 4

1 * 12 – 3

2 * 6 + 1

3 * 4

– 6x2 – x + 2

Step 1A: No GCF

Step 1B: – 1(6x2 + x – 2)

Step 2:Step 3:

6 * 2 = 12 + 4

1 * 12 – 3

2 * 6 + 1

3 * 4

Step 4:

Only the +4 added to the – 3 will equal +1.

And since (+ 4)(– 3) = – # , this verifies these are the two factors needed.

– 6x2 – x + 2

Step 1A: No GCF

Step 1B: – 1(6x2 + x – 2)

Step 5: – 1 (x + 4) (x – 3)

Step 2:Step 3:

6 * 2 = 12 + 4

1 * 12 – 3

2 * 6 + 1

3 * 4

Step 4:

Only the +4 added to the – 3 will equal +1.

And since (+ 4)(– 3) = – # , this verifies these are the two factors needed.

– 6x2 – x + 2

Step 1A: No GCF

Step 1B: – 1(6x2 + x – 2)

Step 5: – 1 (x + 4) (x – 3)

Step 6: – 1 (x + 4) (x – 3)

2 2

Step 2:Step 3:

6 * 2 = 12 + 4

1 * 12 – 3

2 * 6 + 1

3 * 4

Step 4:

Only the +4 added to the – 3 will equal +1.

And since (+ 4)(– 3) = – # , this verifies these are the two factors needed.

– 6x2 – x + 2

Step 1A: No GCF

Step 1B: – 1(6x2 + x – 2)

Step 5: – 1 (x + 4) (x – 3)

Step 6: – 1 (x + 4) (x – 3)

6 6

Step 7-9: – 1(3x + 2) (2x – 1)

Step 2:Step 3:

6 * 2 = 12 + 4

1 * 12 – 3

2 * 6 + 1

3 * 4

Step 4:

Only the +4 added to the – 3 will equal +1.

And since (+ 4)(– 3) = – # , this verifies these are the two factors needed.

(you may use GeoGebra).

x2 + 4x + 3

x2 + 7x + 6

x2 + 9x + 8

x2 + 10x + 9

x2 + 2x − 3

x2 + 5x − 6

x2 + 7x − 8

x2 + 8x − 9

The problems on this page and the next can be used as extra practice or as homework.

x2 − 2x − 3

x2 − 5x − 6

x2 − 7x − 8

x2 − 8x − 9

x2 − 4x + 3

x2 − 7x + 6

x2 − 9x + 8

x2 − 10x + 9

x practice or as homework.2 + 4x + 3

x2 + 7x + 6

x2 + 9x + 8

x2 + 10x + 9

x2 + 2x − 3

x2 + 5x − 6

x2 + 7x − 8

x2 + 8x − 9

x2 − 2x − 3

x2 − 5x − 6

x2 − 7x − 8

x2 − 8x − 9

x2 − 4x + 3

x2 − 7x + 6

x2 − 9x + 8

x2 − 10x + 9

Download Presentation

Connecting to Server..